Zgodovinski prizori in portreti za zdravilišče Rogaška Slatina v zgodnjem 20. stoletju - Vidmar, Polona (Acta historiae artis Slovenica, 2023)
The paper analyses five paintings depicting momentous events in the history of the Rogaška Slatina (Rohitsch-Sauer-brunn) Spa, three portraits of the members of the Habsburg House, and two portraits of the members of the Karađorđe-vić dynasty. It focuses on the literary sources that influenced the choice of motives and the iconography of the historical scenes that were painted for the most prominent hall of the former Kurhaus (now the Grand Hotel Rogaška). Based on archival sources the paper sheds light on the hitherto unknown historical and social context of public commissions. It discusses the role of the commissioner, the spa’s director at the time, Franz Mulli, Doctor of Law, and his connections to the representatives of the Styrian Provincial government and cultural institutions, that resulted in hiring the then highly esteemed Graz painter Alfred von Schrötter. In the new regime established after WWI, Mulli’s successor Franc Šter, Doctor of Law, commissioned a historical scene and portraits by the then highly valued portrait painter in Ljubljana, Ivan Vavpotič.
Keywords: art commission; health resorts; historical painting; historično slikarstvo; Mulli, Franz; portraits; portretno slikarstvo; Rogaška Slatina (Slovenia); Rogaška Slatina (Slovenija); Schrötter, Alfred von; Slovensko slikarstvo; umetnostna naročila; Vavpotič, Ivan; zdravilišča